IMPLEMENTASI DIVERSI SEBAGAI WUJUD PERLINDUNGAN HAK ANAK - Kuswendari Listyaningtri H. dan Apectriyas Zihaningrum, Nadia Oktaviani Zulfa (GEMA, 2015)
The journal is discussing the implementation of diversion as a protection of the rights of child, which to be reviewed in the fulfillment of human rights and the rights of the child. This type of research is a normative legal research prescriptive with secondary data sources through technical literature study with qualitative data analysis (content analysis). Against the backdrop of the rise of the fulfillment of child rights issues that violate human rights, the concept of diversion arises from the idea of humanity and poured in legislation. Diversionâs pratice are things that should be monitored in order to realize the Restorative Justice with the principle of the best interests of the child as the embodiment of the fulfillment of human rights and rights of the child.